Upper and Lower Semicontinuity of Solution Sets for Parametric Generalized Vector Quasi-Equilibrium Problems (Communications in Mathematical Research, 2021)
In this paper, two kinds of parametric generalized vector quasi-equilibriumproblems are introduced and the relations between them are studied. The upper andlower semicontinuity of their solution sets to parameters are investigated.
Keywords: parametric generalized vector quasi-equilibrium problem; solution set; upper semicontinuity; lower semicontinuity; set-valued mapping.